Feasibility of a Critical Care Ultrasound Curriculum Delivered Through Facebook - Li, Shiqan (Cureus, 2019)
Purpose To investigate the feasibility of adjunct critical care ultrasound (CCUS) curriculum via Facebook, and evaluate its impact on fellow’s interest and knowledge acquisition. Materials and methods All University of Southern California (USC), Pulmonary, Critical Care and Sleep Medicine (PCCM) fellows were provided the usual CCUS curriculum. The intervention group provided access to an adjunct CCUS curriculum delivered via Facebook. Results Out of a total of 21 fellows, 10 (47.6%) participated in the Facebook group. The mean number of posts viewed was 24 with a range of 8 to 36 (total 41). Of those who responded, 56% responded Facebook was effective, 89% felt the content was moderate to very useful, 56% responded it enhanced their CCUS education, and 44% stated it motivated them to learn. Pre- and post-testing was done using paired t-tests; the average pre and post-intervention raw score means (of a total of 41 questions) for controls were 35.4±2.9 and 38.2±1.75 (p=0.005). Intervention scores were 37.56±1.94 and 38.0±1.50 (=0.602).  Conclusions Evaluating the feasibility of the adjunct CCUS curriculum using social media, we found that Facebook may be acceptable to fellows, however, there was no significant improvement in knowledge. For learners, social media is easily accessible, widely available, and may motivate increased interest in learning and its potential uses warrants further study.